2003
DOI: 10.1021/ac034936c
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Phase Nanoscale Liquid Chromatography−Mass Spectrometry of Underivatized Oligosaccharides at Low-Femtomole Sensitivity

Abstract: We here describe the online liquid chromatography (LC) electrospray ionization mass spectrometry (MS) of underivatized glycans using a nanoscale normal-phase amide column at a flow rate of 300 nL/min. Retention on the amide column is based on polar interactions of the oligosaccharide hydroxyl groups with the stationary phase, and thus, the retention time predictably increases with elongation of the oligosaccharide chain. The system is characterized by its high chromatographic resolution, which routinely allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 36 publications
1
96
0
Order By: Relevance
“…Although ESI-MS is a popular choice for glycan analysis, poor ionization efficiency of many native glycan molecules in positive mode ESI has led researchers to investigate ways to improve glycan ionization [13][14][15][16]. Due to the poor basicity of glycans, formation of sufficient MH ϩ ion abundance in positive mode ESI is difficult to achieve [13][14][15][16]. Negative mode ESI offers ionization advantages for the analysis of glycans, however, positive mode ESI is also desirable due to its capability to generate different MS/MS glycan ion fragmentation than typically observed in negative mode ESI-MS/MS [17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although ESI-MS is a popular choice for glycan analysis, poor ionization efficiency of many native glycan molecules in positive mode ESI has led researchers to investigate ways to improve glycan ionization [13][14][15][16]. Due to the poor basicity of glycans, formation of sufficient MH ϩ ion abundance in positive mode ESI is difficult to achieve [13][14][15][16]. Negative mode ESI offers ionization advantages for the analysis of glycans, however, positive mode ESI is also desirable due to its capability to generate different MS/MS glycan ion fragmentation than typically observed in negative mode ESI-MS/MS [17,18].…”
mentioning
confidence: 99%
“…While this approach has been successful, it increases the complexity of sample preparation, such that many researchers have explored other means by which analysis of underivatized glycans can be performed in positive mode ESI [13,17,18,21]. It has been found that metal and ammonium ion complexes, such as MNa ϩ and MNH 4 ϩ , form readily with contaminant/residual cations in the ESI solution [14,20]. As a result, many of these glycan-cation complexes have been utilized as the molecular ions for analysis via the introduction of salts at low mM concentrations into the ESI solution to maintain consistent ionization efficiency and generate structurally informative MS/MS fragmentation patterns [13, 15- [15,18].…”
mentioning
confidence: 99%
“…However, this approach has been mainly based on the use of analytical columns employing very high flow rates, which adversely affect sensitivity. Recently, this problem has been rectified through the use of capillary amide columns at a flow rate of 300 nL/min, interfaced to IT-MS [74]. The use of nanoLC format permitted the detection of oligosaccharide mixtures at low-femtomole sensitivity.…”
Section: Interfacing Other Chromatographic Techniques To Msmentioning
confidence: 99%
“…The use of nanoLC format permitted the detection of oligosaccharide mixtures at low-femtomole sensitivity. The approach was validated using N-glycans derived from keyhole limpet hemocyanine and horseradish peroxidase [74].…”
Section: Interfacing Other Chromatographic Techniques To Msmentioning
confidence: 99%
“…With an increase in the biological importance of oligo-or polysaccharides associated with cell-cell recognition, protein targeting, and metabolic diseases, polysaccharide and glycol-conjugate research has been attracting more attention [4,5]. Although different ionization methods [6][7][8][9][10][11][12][13] have been developed for the analysis of saccharides, matrix-assisted laser desorption/ionization (MALDI) [8] and ESI [11,[14][15][16][17][18] are the most used ionization methods. MALDI time-of-flight (TOF) MS has been used for the analysis of saccharides, and the sensitivity has been improved to the low femtomole level by reductive amination of the samples [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%